Інформаційне забезпечення інтегрованого звітування - Голов, С. Ф.; Holov, S. F. (Видавництво Львівської політехніки, 2017)
Розкрито взаємозв’язок та відмінності фінансової та інтегрованої звітності. Визначено недоліки сучасних підходів до складання інтегрованої звітності на основі даних обліку. Аргументовано, що система рахунків глобального обліку здатна забез- печити формування фінансових і не фінансових кількісних показників інтегрованої звіт- ності.

The article shows the interconnection and differences of financial statements and integrated report. Proved the importance of integrated performance reporting system to improve the efficiency of corporate governance and their importance in the regulation of economic processes. These facts inormatsiynyh growing requests for performance integrated reporting companies controlled by the body of the company, shareholders and investors, and financial analysts market. The drawbacks of the existing approaches to making integrated report on the basis of accounting date is described. In particular, emphasis on the facts of uncertainty sources and ways of obtaining and converting the information that is essential for users of integrated reporting. Outlined content concepts integrated reporting, in particular, its functional orientation as a management tool for companies creating added value in the short, medium and long term, organized according to the business model of companies. It is proved, that the system of accounts of global accounting is able to insure the formation of financial and non-financial quantitative measures of integrated reporting. Such arguments stem from the fact that the global accounting system is defined as the collection, transformation and provide internal and external users to reliable, relevant and timely financial and non-financial information about past and future options of the company and its environment. The data source for creating an integrated information system of global accounting can be a variety of documents of various departments of the company and any relevant information obtained from outside (including on the internet). It was determined that the source data for creating an integrated information system of global accounting (eg accounts unihrafichnoho accounting) can be a variety of documents of various departments of the company and any relevant information obtained from outside (including on the internet). The number and content of such accounts depends on the selected parameters now integrated reporting. Given that the system integrated reporting key indicators are changes in the capital, it is appropriate to have the relevant category in the form of off-balance sheet accounts for each capital. Thus one possible option would be the integration of financial and non-financial indicators for off-balance sheet accounts.
Information support for integrated reporting
Keywords: інтегроване звітування; інтегрований звіт; облік; фінансова звітність; суттєвість; інформаційне забезпечення; integrated reporting; integrated report; accounting; financial statements; materiality; information support; 657.37